Acute diverticulitis: an ongoing economic burden on the health system. Issue 10 (17th August 2020) - O'Grady, Michael; Turner, Gregory; Currie, William; Yi, Ma; Frizelle, Frank; Purcell, Rachel
Abstract: Background: Acute diverticulitis (AD) is an increasingly common cause of acute hospital admissions. An understanding of its economic burden is necessary to plan resource allocation, and for targeting health research funding. The aim of this study is to obtain an accurate estimate of the cost of AD, accounting not only for the initial episode, but all related costs incurred during long‐term follow‐up. Methods: The study captures a cohort of patients who had an initial admission for AD from 1 January 2012–31 December 2012, and their treatment over a 6‐year period. Cases were identified from a prospectively maintained database, with AD confirmed by computed tomography scan. The primary outcome was total healthcare cost related to AD. Results: The study included 170 patients. The total cost was NZD1 956 859 with a median cost per patient of NZD4814. A total of 57% of the cost was incurred for the initial inpatient admission, with the remaining 43% incurred through re‐admission, follow‐up appointments, investigations and management. Half of the total cost was incurred by 11.8% of the cohort. In multivariate analysis, high cost of care was significantly associated with complicated and recurrent disease, operative intervention and length of stay. Conclusion: This study provides an accurate estimate of the overall cost of AD and its sequelae. There are considerable long‐term costs associated with the index episode and a large proportion of the expenditure is incurred by a small group that included those with complicated disease. These findings are important for healthcare resource allocation and for targeting health research funding. Abstract : This study provides an accurate estimate of the overall healthcare cost of acute diverticulitis and its sequelae. There are considerable long‐term costs associated with the index episode of diverticulitis with only 57% of the cost occurred at initial admission. A large proportion of the expenditure is incurred by a small group that included those with complicated disease. These findings are important for healthcare resource allocation and for targeting health research funding.